2018
DOI: 10.1186/s40824-018-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chondrogenesis of human placenta-derived mesenchymal stem cells via heparin-grafted human fibroblast derived matrix

Abstract: BackgroundFormation of mature and functional articular cartilage is still challenging in cartilage tissue engineering. This study investigates the potential of using heparin-grafted decellularized extracellular matrix (ECM) as a novel growth factor delivery platform towards human placenta-derived mesenchymal stem cells (hPMSCs) chondrogenic differentiation. Human fibroblast-derived extracellular matrix (hFDM) is naturally obtained from in vitro-cultured human lung fibroblasts via a mild decellularization proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…With the onset of myopia with the increase in the rate, there are more and more serious complications caused by high myopia. The main complications of high myopia are scleral staphyloma, retinal hemorrhage, hole, atrophic degeneration, subretinal neovascularization, retinal detachment, glaucoma and cataract, which seriously affect human health (6). TGF -β 1 plays an important role in embryo development, cell differentiation, immune response and tissue regeneration Function (7,8), TGF -β 1 is one of the TGF -β subtypes, which is expressed in sclera, choroid and retina.…”
Section: Discussionmentioning
confidence: 99%
“…With the onset of myopia with the increase in the rate, there are more and more serious complications caused by high myopia. The main complications of high myopia are scleral staphyloma, retinal hemorrhage, hole, atrophic degeneration, subretinal neovascularization, retinal detachment, glaucoma and cataract, which seriously affect human health (6). TGF -β 1 plays an important role in embryo development, cell differentiation, immune response and tissue regeneration Function (7,8), TGF -β 1 is one of the TGF -β subtypes, which is expressed in sclera, choroid and retina.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 enhances chondrocyte differentiation early on by modulating proliferation, increasing alkaline phosphatase activity, and increasing proteoglycan synthesis [ 58 ]. TGF-1 can be released in a sustained manner on human fibroblast-derived ECM–hep for up to 28 days, according to Noh et al [ 31 ] indicating that the interaction between heparin and TGF-1 is safe and effective. Some studies have found that incorporating heparin into hydrogels can improve the chondrocyte phenotype or promote the re-differentiation of dedifferentiated chondrocytes [ 59 ].…”
Section: Application Of 3d Spheroid Culture System To Chondrogenic Di...mentioning
confidence: 99%
“…cADMSCs stored in Hepa-Sal for 12 h showed the highest expression of both genes compared to other solutions. The higher chondrogenic ability of Hepa-Sal might be associated with the inherent nature of heparin as it ensures the secretion of endogenous growth factors such as transforming growth factor β1, vascular endothelial growth factor, and fibroblast growth factor from the cells, thereby promoting chondrogenesis [61,62]. Besides, several studies have shown that the incorporation of heparin in hydrogel can improve the re-differentiation of differentiated chondrocytes and chondrocyte phenotypes [63,64].…”
Section: Discussionmentioning
confidence: 99%